Optimasi Pengelolaan Administrasi Data melalui Sistem Informasi Terintegrasi di Nagari Gunung Rajo (Sinagari) - Yance Sonatha; Aldo Erianda; Safira Putri Nabila (SOTVI - Society of Visual Informatics, 2023)
In the present day, which is characterized by the prevalence of information technology, the primary emphasis for governments is on effectively handling regional administrative data in order to promote transparency and responsiveness. This article presents a research study that investigates the implementation of a web-based information system in Nagari Gunung Rajo, West Sumatra, with the aim of enhancing the effectiveness, precision, and openness of administrative procedures. The waterfall process is employed, encompassing the stages of requirements analysis, design, program code production, and testing. The outcome is a comprehensive system that facilitates the efficient management of population and nagari data for administrators, operators, and general users. This includes user-friendly features such as data import, public complaint handling, and letter filing capabilities. This study presents a novel approach to enhance the efficacy of public services through the utilization of information technology in the effective management of regional administration.